Decay‐accelerating factor 1 deficiency exacerbates Trypanosoma cruzi ‐induced murine chronic myositis - Solana, Maria Elisa (2012)
Introduction: Experimental murine infection with trypanosoma cruzi (TC) has been proposed as a model of human inflammatory idiopathic myositis to study the role of T-cells in its pathogenesis. Absence of decay-accelerating factor 1 (Daf1) has been shown to enhance murine T-cell responses and autoimmunity via increased expression of cytokines, including interferon-ã. Methods: To determine whether Daf1 deficiency can exacerbate TC-induced myositis, C57BL/6 Daf1+/+ and Daf1-/- mice were inoculated with 105 trypomastigotes and their morbility, parasitaemia, histopathology, and T-cellexpansion were studied in the acute and chronic stages. Results: Daf1-/- mice presented lower parasitaemia but higher morbidity, muscle histopathology, and increased spleen number of CD44+ (activated/memoryphenotype) CD4+ and CD8+ T cells. Discussion: An enhanced CD8+ T cell immune specific response may explain the lower parasitaemia levels and the increase in histopathological lesions. We propose the TC-inoculated Daf1-/- mice as a useful model to study T-cellmediatedimmunity in skeletal muscle tissues.